Effect of decrease of physical activity on depression and anxiety after the COVID-19 lockdown: A survey study - Kajtna, Tanja; Vučković, Vojko (Frontiers in Psychology, 2022)
Purpose: We focused on changes in the amount of physical activity and depression and anxiety symptoms in people, who were previously regularly physically active, as they were all members of fitness centers at time of lockdown because of COVID-19. Method: We sampled 150 participants, who participated in the study of which were all members of fitness centres. Depression and anxiety were measured with subscales of PAI and physical activity was measured with GPAQ. Results: We found that depression and anxiety was more present with female participants than male participants, single participants experienced more depression than participants in relationship, unemployed participants experienced more depression and anxiety than employed participants and participants with lower levels of education experienced higher levels of depression and anxiety than participants with higher levels of education. Finally, we found that mental health can be influenced by changes in amount of movement – both anxiety and depression (in whole and its specific dimensions) increase when there is less strenuous work-related activity, less walking or cycling to work and when participants would spend more time each day sitting. Ex- professional athletes are particularly immune to anxiety and depression. Discussion: Mental health has great impact on isolation, the most effective solution to stress relief and anxiety is physical exercise, which was limited or non-existent in the time of pandemic. For future studies we recommend focusing on likelihood of increased depression and anxiety levels in individuals, who were physically active before the isolation period.